Enzymatic pretreatment for the improvement of dispersion and film properties of cellulose nanofibrils. (1st February 2018) - Nie, Shuangxi; Zhang, Kun; Lin, Xuejiao; Zhang, Chenyuan; Yan, Depeng; Liang, Hongming; Wang, Shuangfei
Highlights: Enzymatic pretreatment could improve the dispersion and film properties of CNF. Carboxy groups played pivotal role on dispersion and film properties of CNF. Carboxy groups increased during enzymatic pretreatment. Research results will help roll to roll production of CNF film. Abstract: In the present study, cellulose nanofibrils (CNF) were produced from unbleached eucalyptus pulp, and the effect of enzymatic treatment on the properties of CNF was studied. Moreover, the mechanism of enzymatic treatment on the dispersion and film properties of CNF was speculated. The xylanase pretreatment facilitated the deconstruction of pulp into CNF via mechanical shearing and high-pressure homogenization, while the hemicellulose composition was preserved. Compared to the control, the CNF suspensions made from the xylanase pretreated pulp were more crystalline with higher dispersion, optical and rheological properties. CNF films were produced with a vacuum filtration process. The optical and mechanical strength properties of the CNF films were improved by the removal of hemicellulose. It was found that the carboxyl and hydroxyl groups played key roles in affecting the dispersion and film properties of the CNF. The carboxyl group content increased after the enzymatic pretreatment, which benefits the even distribution of CNF in water. The mechanical strength of the CNF films was further improved by exposing the hydroxyl group when lignin-carbohydrate complexes were de-structured by the enzymes. This study expanded the application of CNF produced from unbleached pulp. The theoretical foundation for stabilizing the CNF suspension and the high-speed dehydration of CNF films were explored for the continuous roll to roll production of CNF film.